Middle segment-preserving pancreatectomy to avoid pancreatic insufficiency: individual patient data analysis of all published cases from 2003-2021 - Pausch, Thomas; Liu, Xinchun; Dincher, Josefine; Contin, Pietro; Cui, Jiaqu; Wei, Jishu; Heger, Ulrike; Lang, Matthias; Tanaka, Masayuki; Heap, Stephen; Kaiser, Jörg; Klotz, Rosa; et al. (Journal of Clinical Medicine, 2023)
Middle segment-preserving pancreatectomy (MPP) can treat multilocular diseases in the pancreatic head and tail while avoiding impairments caused by total pancreatectomy (TP). We conducted a systematic literature review of MPP cases and collected individual patient data (IPD). ...
Gesehen am 05.12.2023